DEGREE OF PREFERENCE OF LIVE FOOD BIOTA OF A FRESHWATER PRAWN MACROBRACHIUM DAYANIJM THROUGH DIFFERENTIAL EQUATION’ MODEL - CHAKRABARTI, SAUMEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
In order o understand the degree of competition coefficient of a prawn species. Macrobrach/ima, dayamua, with different live food biota such as phytoplankton as well as zooplankton, predator- food relationship was drawn through a mathematical differential equation model : d N2/dt=r2N2 x(K2—N2— ßN1)/K2 These equations exhibited a1 = 0.29 and ci2 = 0.18, which indicated negligible inhibition of both phytoplankton as well as zooplinkton on the prawn species. Interestingly, the competition coefficient of the said prawn species with the phytoplanktonic (i) as well as zooplanktonic biota (ß2) were 21.56 and 58.32 respectively, which signifying higher rate of predation on the zooplankton and relatively lower rate on the phytoplankton (ß). So, these results probaNy indicate that zooplankton was considered as preferred live food while phytoplankton as ordinary food item.